Preliminary Evaluation of Banana Fiber Opening Performance using a Multi-Axis Air-Injected Rotary Arm Fiber Opening Machine (MAIRA-FOM) - Khamis, Nur Suhailah; Shaari, Muhammad Farid; Mohd Asrah, Norhaidah; Roslee, Mohd Azim Faris (Progress in Engineering Application and Technology, 2026)
Breaking of fibers during the fiber opening process has led to the development of a novel fiber opening technique that utilizes an air injection–assisted rotational beater. However, the full potential of this technique is still under investigation, particularly in terms of optimizing its process parameters. Hence, this research was conducted as a preliminary evaluation of a newly developed machine known as the Multi-Axis Air Injection Rotary Arm Fiber Opener Machine (MAIRA-FOM). The aim of this study was to investigate the correlation between fiber load and processing time on fiber opening efficiency. Two different raw, unopened fiber loads of 50 g and 150 g were processed at three processing durations of 5 minutes, 10 minutes and 15 minutes. The weights of both opened and unopened fibers were measured to determine the fiber opening efficiency. The results indicate that both fiber load and processing time significantly affect the opening efficiency, exhibiting a linear relationship. The highest efficiency achieved was 52% at a processing time of 15 minutes, which was significantly higher than the 28% efficiency obtained at 5 minutes. Additionally, a higher fiber load of 150 g resulted in improved separation efficiency compared to the lower fiber load of 50 g.